Analisa Penggunaan Metode AHP Untuk Sistem Pendukung Keputusan Dalam Pemilihan Calon Kepala Desa di Klambir Lima - Yanti Yusman (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Indonesia is a demogratic country whith has general elections according to its level whitch with this general election provides convenience in the sustainability of development in an area but not in klambir lima this procedure aims to analyze the use of the AHP method to determine a decision support system in the election of village head candidates in klambir lima which is part of teh deliserdang district of  medan city in the election og village heads often has inequality in the election, it is felt that this papar uses the AHP method in analyzing descriptive qualitative data, by collecting data by interviewing the community in the election of  village head candidates,.with the help of the community in klambir lima, it provides convebience later in determining or selecting village head candidates